Stress Appraisals and Coping across and within Academic, Parent, and Peer Stressors: The Roles of Adolescents' Emotional Problems, Coping Flexibility, and Age - Melanie J. Zimmer-Gembeck; Ellen A. Skinner (MDPI AG, 2024)
The aim of this study was to determine whether adolescents' emotional problems, coping flexibility, age, and stress appraisals account for ways of coping, which include engagement and disengagement coping, with academic-, parent-, and peer-related stressful events. Stress appraisals were defined as perceived threats to the psychological needs of relatedness, competence, and autonomy. Models were fit at a higher order level, indicated by adolescents' appraisals and intended ways of coping with stress in three domains (i.e., academic, parent, and peer) and tested at the lower level within each domain. Adolescents (N = 410; age 10-15; Mage = 12.5; 50% girls) reported their emotional problems (combined depressive and anxiety symptoms) and coping flexibility six months prior to completing an analogue task. The task involved viewing six short film clips portraying stressful events (e.g., obtaining a worse than expected exam grade or arguing with a parent) and reporting three stress appraisals and eight ways of coping after each stressor. The ways of coping were analyzed as four composite scores reflecting engagement coping (active coping, self-reliance) or disengagement coping (withdrawal coping, helplessness). In structural equation models, adolescents who appraised more threat reported more withdrawal coping and helplessness but also more active coping and self-reliance. Adolescents with more emotional problems appraised more threat and anticipated using less constructive ways of coping, whereas adolescents higher in coping flexibility intended to use more constructive ways of coping, with these associations sufficiently modeled at the general (across stress domains) level. Improvement in the model fit was found when appraised threat-coping associations were modeled at the lower (specific stressor domain) level, suggesting differences by stressor domain. Age was associated with more self-reliance and helplessness, with self-reliance being specific to parent stressors and helplessness specific to peer stressors.